Role of Autophagy in Alcohol and Drug-induced Liver Injury - Williams, Jessica A. (Food Chem Toxicol, 2019)
Alcohol-related liver disease (ALD) and drug-induced liver injury (DILI) are common causes of severe liver disease, and successful treatments are lacking. Autophagy plays a protective role in both ALD and DILI by selectively removing damaged mitochondria (mitophagy), lipid droplets (lipophagy), protein aggregates and adducts in hepatocytes. Autophagy also protects against ALD by degrading interferon regulatory factor 1 (IRF1) and damaged mitochondria in hepatic macrophages. Specifically, we will discuss selective autophagy for removal of damaged mitochondria and lipid droplets in hepatocytes and autophagy-mediated degradation of IRF1 in hepatic macrophages as protective mechanisms against alcohol-induced liver injury and steatosis. In addition, selective autophagy for removal of damaged mitochondria and protein adducts for protection against DILI is discussed in this review. Development of new therapeutics for ALD and DILI is greatly needed, and selective autophagy pathways may provide promising targets. Drug and alcohol effects on autophagy regulation as well as protective mechanisms of autophagy against DILI and ALD are highlighted in this review.